Analysis the Impact of Enterprise Resource Planning (ERP) and Big Data in Improving Company Performance : A Systematic Literature Review - Nyimas Aulia Gandasari; Mukhtaruddin Mukhtaruddin (Jurnal Riset Akuntansi, 2025)
This study conducts a systematic literature review (SLR) exploring the Impact of Enterprise Resource Planning (ERP) and Big Data technologies in Improving Business Performance across global sectors. In the context of Industry 4.0, businesses are rapidly adopting the latest systems for operational efficiency. Research shows that ERP significantly improves business performance in various aspects, resulting in significant benefits for companies. Big Data is recommended as a tool for improving business processes; when combined with ERP, it enables effective and efficient production of useful outputs for companies. This SLR brings together a variety of articles from 2019-2025 and highlights a significant positive correlation between ERP, Big Data, and Business Performance of Companies. Although the relevance of these technologies is recognized, discussions on this topic in Indonesia are still limited. This study aims to encourage a deeper understanding and further research on ERP and Big Data.